DINAMIKA N MINERAL AKIBAT APLIKASI PUPUK NPK KEBOMAS BERBASIS AMONIUM DAN NITRAT 25-7-7 PADA TANAMAN BUNCIS - Sanindya Rivaliati; Retno Suntari; Cahyo Prayogo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2017)
Nitrogen is needed by plants in a sufficient level. This study was aimed to understand the influence of NPK Kebomas ammonium and nitrate based 25-7-7 combined with Petrobiofertil fertilizer on soil chemical properties and common bean production. Treatments tested in this study were P0 (control), P1-P4 (NPK 25-7-7 + nitrate 0-3%), P5-P8 (NPK 25-7-7 + nitrate 0-3% + Petrobiofertil). The nine treatments were arranged in a randomized block design with three replicates. The results showed that application of NPK fertilizer 25-7-7 combined with Petrobiofertil fertilizer gave significant effects on nitrogen, ammonium, nitrate, phosphorus, potassium and pH of the soil studied. The addition of fertilizer (NPK 25-7-7 + Nitrate 3%) + Petrobiofertil affected plant weights, weight of pods, weight of seeds, weight of skins and the number of pods were higher than other treatments